Catalogo de los Membracidae (Homoptera) de Nicaragua - Maes, J.-M.
(Es, Es)
Ilus., 56 ref.
Keywords: CLASIFICACION; MEMBRACIDAE; HOMOPTERA; INSECTA; HUESPEDES; ENEMIGOS NATURALES; DISTRIBUCION GEOGRAFICA; NICARAGUA; REVISTA NICARAGUENSE DE ENTOMOLOGIA